Study of efficacy of hyperbaric oxygen therapy in chronic wounds in diabetic patients - Bhaskar, N.; Kamble, Mayuri A. (International Journal of Research in Medical Sciences, 2025)
Background: Diabetic patients are prone to chronic wounds that are difficult to heal due to impaired blood flow, immune dysfunction, and prolonged hyperglycemia. Hyperbaric oxygen therapy (HBOT) has been proposed as an adjunctive treatment for diabetic wounds. This study aimed to evaluate the efficacy of HBOT in treating chronic wounds in diabetic patients. Methods: A prospective observational study was conducted at Sassoon General Hospital, Pune, Maharashtra from July 2022 to March 2024. A total of 34 diabetic patients with chronic non-healing ulcers were consecutively recruited and randomized into two groups: the test group (standard wound care + HBOT) and the control group (standard wound care only). Primary parameters included wound healing rate and reduction in ulcer area, while secondary parameters involved infection rates, time to appearance of serous discharge, and hospital stay duration. Data were analyzed using statistical package for the social sciences (SPSS) 26.0, with significance set at p<0.05. Results: The HBOT group showed a significantly greater reduction in ulcer area, granulation tissue formation was notably faster compared to the control group. Infection rates were lower in the HBOT group, with a higher proportion of sterile cultures on day and HBOT patients also had a shorter hospital stay compared to controls. Conclusions: HBOT significantly improved wound healing rates, infection control, and reduced hospital stay duration in diabetic patients with chronic wounds.